Utilization of Fly Ash and Bottom Ash from Steam Power Plants (PLTU) as Soil Amendments for Tomato Plants (Solanum lycopersicum L.) - Wiesje Junnieke Nathsuo Kumolontang; Meldi Tineke Magdalena Sinolungan; Rafli Irlan Kawulusan; Yakni Kamagi; Wulan Patadjenu (Jurnal Penelitian Pendidikan IPA, 2025)
Fly ash and bottom ash are waste produced from burning coal in the Steam Power Plant industry. The higher the coal consumption, the higher the FABA waste produced. However, despite the abundant production, this waste has not been optimally managed and utilized. This research aims to determine the effect of using FABA as an ameliorant in planting media for tomato plants. This research used the Completely Randomized Design (CRD) method which consisted of 3 treatments with repetition 4 times to obtain 12 experimental units (polybags). The results of the research indicate that the use of coal waste, namely fly ash and bottom ash as an ameliorant in planting media, has a significant influence on plant height, number of flowers, number of fruits, and fruit weight of tomato plants. Planting media with a composition of 50% soil plus 50% fly ash (treatment A) yielded the lowest results among the three treatments. Meanwhile, the planting medium composition of 50% soil plus 50% bottom ash (treatment B) yielded the best results, exceeding the use of 100% soil (treatment O/control). Bottom ash as an ameliorant has a positive influence on the growth and production of tomato plants.